Using community of practice to characterize collaborative essay prompt writing and its role in developing language assessment literacy for pre-service language teachers. (October 2021) - Ho, Eric C.; Yan, Xun
Abstract: Conceptualizing skills for creating language assessments as an important component of language assessment literacy (LAL), this study investigates the activities of essay prompt writing by pre-service teachers for a post-admissions English placement test (EPT) at a large US university, as an effort to explore the potential of collaborative assessment practices in promoting LAL development. Five pre-service teachers, who are novice prompt writers, participated in a semester-long content development process for the EPT. Adopting a community of practice (CoP) perspective, we qualitatively examined group discussions, individual interviews, and written peer feedback and revisions on essay prompts among the prompt writers. Our findings suggest the important role of collaboration in the development of LAL skills related to creating assessments for individual prompt writers.